Increased Turnover of Beta 2 Microglobulin in Circulation serves as Diagnostic and Prognostic Marker for Malignant Lymphoma; A Case Control Predictive Model for Lymphoma Diagnosis: Beta 2 microglobulin as a diagnostic and prognostic marker - Mumtaz, Tamseela; Iqbal, Muhammad Amir; Roohi, Nabila; Akhtar, Muhammad Waheed (Pakistan Journal of Health Sciences, 2023)
Indolent and aggressive hematopoietic cancer shed lot of Beta 2 microglobulin in interstitial fluid thus increasing the level of B2M in hematological malignancies. Objectives: To set forward B2M as potential biomarker for the detection and stage of malignant lymphoma. Methods: Serum of newly diagnosed Hodgkin’s and non-Hodgkin’s lymphoma patients presented to physician prior to any surgical or medicinal treatment were collected and evaluated through sandwich type of ELISA for the possible elevation of B2M. B2M concentrations in healthy individual’s serum (control group) were also detected. Mean values of B2M in all three groups were compared by applying one-way analysis of variance to determine the significant difference. Results: The serum of Hodgkin’s Lymphoma patients depicted 5 folds higher B2M concentration than the healthy subjects, while NHL showed more concentration of circulating B2M where it was 6-fold higher than healthy subjects. Moreover, the advanced stage of the disease with involvement of distant site or organ portrayed increase shedding of MICA 1 chain in circulating blood than localized or regional disease. Conclusions: Elevated serum B2M concentrations in blood surely a sign of neoplastic disease involving nucleated cell like lymphoma and its enhanced expression in distantly spreading disease proved it as a prognostic marker as well